Notion of failed State: legal consequences from international and Ecuadorian constitutional law, 2019-2022 - Guerrero Salgado, Efrén Ernesto; Merizalde Rodríguez, Nicolás (Instituto de Altos Estudios Nacionales IAEN, 2024)
This article explores the legal consequences of the application of the ‘failed state’ concept, from the perspective of international law and Ecuadorian jurisprudence. It seeks to determine whether the social protests, the increase in criminal violence, citizen insecurity and the violation of human rights that occurred in Ecuador between 2019 and 2022 are a symptom of this fracture, that is, of a failed state. The resolutions of the United Nations system, the regional system for the protection of human rights and rulings of the Constitutional Court (CC) are referred to. The CC documents would expose whether the CC adopted exceptional security measures in a disproportionate manner or whether it promoted a solid institutionality for the protection of human rights. The authors suggest that different elements point to a crisis on several fronts, yet it does not amount to a failed state. Finally, they recommend the responsible and critical use of this concept, as greater analytical capacity in future research depends on it.